Endophthalmitis A Guide to Diagnosis and Management (Springer Singapore, 2018)
This book is an on-the-go resource on all aspects of endophthalmitis essential for practicing ophthalmologists and fellows in training. Endophthalmitis is a devastating condition of the eye. It occurs after surgery, trauma and by endogenous spread of infection. Endophthalmitis: A Guide to Diagnosis and Management deals comprehensively on all aspects of endophthalmitis management-the clinical and applied clinical aspects including the microbiology of the infecting organisms, pharmacokinetics of drugs used in management, investigations into cluster infection, and prophylaxis. An exclusive section is devoted to understanding the clinical trials in endophthalmitis and its analysis.